Reproducibility of Serum 25-Hydroxyvitamin D and Vitamin D-Binding Protein Levels Over Time in a Prospective Cohort Study of Black and White Adults - Sonderman, Jennifer S. (Oxford University Press, 2012)
Prospective epidemiologic studies generally rely on 1 baseline biologic sample from participants for measurement of prediagnostic biomarkers, assuming that 1 measurement adequately represents the participant's “typical” level. The body of work assessing the reproducibility of circulating serum 25-hydroxyvitamin D (25(OH)D) levels over time focuses almost exclusively on populations of European descent, and data for vitamin D-binding protein (VDBP) are virtually nonexistent. Thus, the authors measured levels of serum 25(OH)D and VDBP twice in samples collected between 2005 and 2008 from 225 participants (155 black, 70 white) in the Southern Community Cohort Study. Reproducibility for 25(OH)D was uniformly high, with adjusted intraclass correlation coefficients (ICCs) of 0.84 (95% confidence interval (CI): 0.79, 0.88) for blacks and 0.92 (95% CI: 0.87, 0.95) for whites, and there was substantial agreement for assignment of 25(OH)D quartile (κ = 0.83, 95% CI: 0.78, 0.87) and vitamin D adequacy status (κ = 0.76, 95% CI: 0.69, 0.83). VDBP levels were highly stable over time, with adjusted ICCs of 0.97 (95% CI: 0.96, 0.98) for blacks and 0.96 (95% CI: 0.93, 0.97) for whites. These findings suggest that single, baseline 25(OH)D and VDBP serum measurements provide reasonably representative measures of these compounds for both white and black adults, demonstrating their utility as epidemiologic biomarkers in prospective studies.